Chocolate nations living and dying for cocoa in West Africa - Órla Ryan (New York, NY Distributed in the USA exclusively by Palgrave Macmillan, 2011)
Ghana is cocoa -- Cocoa wars -- Child labour -- Follow the money -- From bean to bar -- Fairtrade myths and reality -- Trading games -- Building a sustainable future.
Includes bibliographical references and index.
Keywords: Cocoa trade--Ghana.